A comparative study on the effects of rote learning of short texts and sentence writing on high school students’ vocabulary retention : - Nguyễn, Thị Mỹ Huyền (Trường đại học Cần Thơ, 2018)
The research aims to examine the effects of RL of short texts on high school students’ vocabulary retention. It also attempts to investigate the effects of sentence writing on the participants’ vocabulary retention. Importantly, the research would compare the effects of the two VLSs to find out whether there is any difference between their effects on high school students’ vocabulary retention.